The range and limitation of sub-national regime variations under electoral authoritarianism: The case of Russia. Issue 3 (27th May 2019) - Ross, Cameron; Panov, Petr
ABSTRACT: As has been demonstrated by scholars, different levels of a polity may encompass different political regimes. In this study we examine variations in regional political regimes which have developed under Russia's system of electoral authoritarianism. Comparing the results of two cycles of regional assembly elections (2008–12 and 2013–17) we analyse and compare elections results and levels of electoral contestation in both the party list (PL) and single member district (SMD) contests. This allows us to identify the range of sub-national regime variations: 'hegemonic authoritarian', 'inter-elite bargain authoritarian', 'clearly-competitive authoritarian', and 'moderately-competitive authoritarian' regions. Approximately half of the regions demonstrate stable electoral patterns across both cycles. At the same time, none of the regions go beyond the authoritarian limitations imposed by the Russian regime. The variation is explained by a combination of structural and agency factors with a prevalence of the latter.